II PLANO NACIONAL DE REFORMA AGRÁRIA: UMA ANÁLISE A PARTIR DOS ASSENTAMENTOS RURAIS EM RORAIMA - Cardoso, Carlos Alberto de Sousa (2009)
This study analyzes the II National Plan for Agrarian Reform (II Plano Nacional de Reforma Agrária II PNRA) from the reality of the families settled and the action of rural social movements and the rural trade union movement in the state of Roraima. Firstly, a review of the agrarian issue in Brazil was carried out in order to examine the way in which the ownership and the use of land have been proceeding in this society. The agricultural development process in Brazil and the way in which, historically, the State has intervened politically toward an agro-exporter model is then discussed. An analysis of how, with the increased presence of capitalism and of industrialization, strong transformations in society have occurred then follows. Brazil is no longer a principally rural country and has become a more urban society. The expansion of capitalism and the deepening of a conservative modernization model for agriculture, in the post-1964 period, have resulted in strong occupation of the Amazon Region, as a way to reduce social conflicts in other regions. The state of Roraima has suffered the implications of this expansion receiving a great number of migrants in the past decade, being transformed from a state in which it was easy to obtain land, as stated in governmental publicity, into a region where agro-business and the landless people (sem-terra) are in dispute over territory. This situation has been aggravated by the election of a government of a popular‟ nature, in 2002, when the landless of Roraima occupied mainly federal owned land, in an organized manner, in the form of a trade union and rural movement. During this period, the government launched the II PNRA in order to address the demands for agrarian reform made by wide sectors of society. However, during its mandate, Luiz Inácio Lula da Silva‟s government has been distancing itself from popular sectors and, concomitantly, moving closer to the national bourgeoisie, thus giving continuity to the neoliberal model of its predecessor. On the other hand, the landless and the rural social movements have extended their occupation of land in Roraima in order to pressurize INCRA, the main executor of the aforementioned plan, to effectively settle the families which have been camped out on federal owned land. This new scenario has led to the arising of a situation of conflict which pressurized and contributed to the removal of several superintendents of INCRA, six, during Lula‟s government. The results of the investigation show that II PNRA, in Roraima, has been implemented partially and precariously and that it has achieved only the first stages of the agrarian reform program, that of the distribution of plots, and other small directed and focused actions, and that even this came about through strong social mobilization and pressure.